Behavioral responses of Anopheles species (Culicidae: Diptera) with varying surface exposure to pyrethroid‐treated netting in an excito‐repellency test system. Issue 2 (17th November 2016) - Tainchum, Krajana; Nararak, Jirod; Boonyuan, Wasana; Bangs, Michael J.; Chareonviriyaphap, Theeraphap
ABSTRACT: Indoor Residual Spray (IRS) with insecticides has been a procedure used for decades to protect humans from biting mosquitoes and potential vectors of pathogens. The objective of this study was to determine the responses of three wild‐caught species of malaria vectors exposed to pyrethroids of three different surface coverage percents using an excito‐repellency test box. Each species was exposed to three insecticide‐treated surfaces at varying exposure levels (full coverage, 50%, and 25% of the maximum allowable by the test system) to a single standard field dose of either lambda‐cyhalothrin or alpha‐cypermethrin. Larger numbers of mosquitoes escaped the treated chambers in the direct contact test compared to the spatial repellent chambers in all three different treated surface exposures. No significant differences in the percent of escaped mosquitoes were detected in the 50% and full coverage surface coverage exposures, whereas the 25% coverage produced significantly lower avoidance responses for both compounds. This study found that varying levels of surface exposure with synthetic pyrethroids can impact the behavioral avoidance responses of Anopheles ; however, it may also be possible to reduce the amount of coverage to achieve similar avoidance actions. This information may assist policy makers in designing more cost effective strategies involving residual insecticides to control mosquito vectors.